2018
DOI: 10.1080/20786190.2018.1426901
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric profile and complications in patients with diabetes mellitus seen at Maluti Adventist Hospital, Lesotho

Abstract: Background: Patients attending outpatient departments for follow-up of diabetes mellitus (DM) may seem content about the control of their disease. However, complications resulting from DM may present before diagnosis and treatment initiation or continue to develop while on treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The participants in this study, though recruited via random convenience sampling, were predominantly female (4:1 ratio to males). Though this is not the typical gender pattern for T2DM reported in higher income countries, 12 it is consistent with the findings of other studies on T2DM in Lesotho [25][26][27] and neighbouring South Africa. [28][29][30] This may be explained by the fact that, in sub-Saharan Africa and other developing regions, the most prominent risk factor, which is obesity, is more common in women than in men, 12 as is also evident in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The participants in this study, though recruited via random convenience sampling, were predominantly female (4:1 ratio to males). Though this is not the typical gender pattern for T2DM reported in higher income countries, 12 it is consistent with the findings of other studies on T2DM in Lesotho [25][26][27] and neighbouring South Africa. [28][29][30] This may be explained by the fact that, in sub-Saharan Africa and other developing regions, the most prominent risk factor, which is obesity, is more common in women than in men, 12 as is also evident in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that the current study was performed at only two public healthcare facilities may limit the generalisation of the findings. The findings are, however, very similar to those recorded for outpatients with T2DM who rely on the public health sector in Lesotho, 27,36 as well as in other parts of the sub-Saharan region. 3…”
Section: Limitationssupporting
confidence: 80%
“…A wide variation was noted in the prevalence of diabetic peripheral neuropathy across the studies, with prevalence ranging from 4% in a study conducted in Eritrea 51 to 83.3% in a study conducted in Nigeria. 68 A study by Makwero and colleagues 109 conducted in Lesotho reported the lowest prevalence of diabetic retinopathy of 4.7%, while the study by Megalla and colleagues 97 conducted in Egypt reported the highest (90%).…”
Section: Resultsmentioning
confidence: 97%
“…The majority of studies were performed in Eastern African countries (44, 40.4%). 3 16-58 The proportion of studies conducted in Western, Northern, Southern and Central Africa was 22% (n=24 studies), 3 59-80 16.5% (n=18 studies), [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] 15.6% (n=17 studies) [100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] and 8.3% (n=9 studies), 3 59 117-123 respectively. Three studies were conducted in more than one region of Africa (Western, Central and Eastern).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…These variables provided information on cross-national factors that affect and reflect health outcomes-low and high BMI and child mortality. In addition, these variables could be used to generate complex but accurate models [41,42].…”
Section: Study Variablesmentioning
confidence: 99%